FREKUENSI PEMBERIAN GROW QUICK LB TERHADAP PERTUMBUHAN BIBIT ANGGREK DENDROBIUM PADA STADIA KOMUNITAS POT - SURTINAH SURTINAH; ENNY MUTRYARNY (Jurnal Ilmiah Pertanian, 2013)
ABSTRACTThis research was held at screen house of Fakultas Pertanian Unilak, thisexperiment is a kind of research that using 1 factor of 2 treatments which the Grow QuickLB fertilizer giving 3 times a day and the Grow Quick LB fertilizer giving 6 times a day.The growth of Anggrek Dendrobium seedling that observed are the length of bud, thelength of bud’s leaves, the width of bud’s leaves, and the number of bud’a leaves. Theabtaining data was analyze which used t – Test. The result of the 3 times giving GrowQuick LB fertilizer treatment a day is the best growing of Anggrek Dendrobium.